Age estimation using permanent mandibular second molar teeth in a Thai population - Phuwadon Duangto (2020)
© 2020, © 2020 Australian Academy of Forensic Sciences. The purposes of this study were to develop age estimation equations and to validate the accuracy of the resulting equations in a Thai sample. A total sample of 640 digital panoramic radiographs aged from 7–14 years was collected. The sample was divided into two sets as follows: the training set and the test set. To evaluate the dental maturation, the permanent mandibular second molar teeth were separated into seven stages (A to G) according to the Demirjian et al. classification system. The dental age estimation equations were developed, using quadratic regression analysis. The results showed that the equations had a strong correlation coefficient between the score and the chronological age in both sexes. Moreover, the accuracy of the resulting equations was validated in the test group, and these results showed high accuracy for dental age estimation with low values of the mean error in both sexes. The mean absolute error values were 0.80 years in males, and 0.70 years in females. The root mean square error values were 0.93 years in males, and 0.89 years in females. In conclusion, the age estimation equations based on developing permanent mandibular second molar teeth in this study provided accurate dental age estimation.